Influence of Mechanical Loading on the Process of Tribochemical Action on Physicochemical and Biopharmaceutical Properties of Substances, Using Lacosamide as an Example: From Micronisation to Mechanical Activation - Elena V. Uspenskaya; Ekaterina Kuzmina; Hoang Thi Ngoc Quynh; Maria A. Komkova; Ilaha V. Kazimova; Aleksey A. Timofeev (MDPI AG, 2024)
Many physical and chemical properties of solids, such as strength, plasticity, dispersibility, solubility and dissolution are determined by defects in the crystal structure. The aim of this work is to study in situ dynamic, dispersion, chemical, biological and surface properties of lacosamide powder after a complete cycle of mechanical loading by laser scattering, electron microscopy, FR-IR and biopharmaceutical approaches. The SLS method demonstrated the spontaneous tendency toward surface-energy reduction due to aggregation during micronisation. DLS analysis showed conformational changes of colloidal particles as supramolecular complexes depending on the loading time on the solid. SEM analysis demonstrated the conglomeration of needle-like lacosamide particles after 60 min of milling time and the transition to a glassy state with isotropy of properties by the end of the tribochemistry cycle. The following dynamic properties of lacosamide were established: elastic and plastic deformation boundaries, region of inhomogeneous deformation and fracture point. The ratio of dissolution-rate constants in water of samples before and after a full cycle of loading was 2.4. The lacosamide sample, which underwent a full cycle of mechanical loading, showed improved kinetics of API release via analysis of dissolution profiles in 0.1 M HCl medium. The observed activation-energy values of the cell-death biosensor process in aqueous solutions of the lacosamide samples before and after the complete tribochemical cycle were 207 kJmol−1 and 145 kJmol−1, respectively. The equilibrium time of dissolution and activation of cell-biosensor death corresponding to 20 min of mechanical loading on a solid was determined. The current study may have important practical significance for the transformation and management of the properties of drug substances in solid form and in solutions and for increasing the strength of drug matrices by pre-strain hardening via structural rearrangements during mechanical loading.